The Role of Religious-Based Empowerment in Enhancing Asnaf Entrepreneurs’ Success: Evidence from Jogokariyan Mosque, Indonesia - Rarasati, Indin; Amin, Hanudin (Universitas Muhammadiyah Yogyakarta, 2025)
Mosque-based Islamic microfinance uniquely combines religious values with community economic empowerment. This study examined the business success of Micro, Small, and Medium Enterprises (MSMEs) that receive financing and mentoring from Jogokaryan Mosque. The measurement of business success was viewed from the perspective of Maqasid Sharia, which includes business experience, business justice, business welfare, financial wisdom, and one additional variable: the quality of worship. The research method used was the Asnaf Muslimpreneur Success Index (AMSi) to gauge the level of business success among MSME actors. The study population consisted of MSME actors who received financing and participated in a series of programs organised by Jogokaryan Mosque. A sample of 56 respondents was obtained using a purposive sampling technique. The result showed that the level of business success among MSMEs associated with Jogokaryan Mosque was categorised as medium-high success. This success was beneficial for MSME actors and could be further enhanced through a series of supporting programs with consistent intensity. The implication of this study was to evaluate the empowerment program offered by Jogokaryan Mosque and enhance the quality of both program delivery and financing. In fact, the goal was to boost business success and empower MSME actors in their entrepreneurial endeavours